Abdominal compartment syndrome in a monochorionic‐triamniotic triplet pregnancy complicated by feto‐fetal transfusion syndrome. Issue 9 (7th July 2021) - Obata, Kenta; Tanimura, Kenji; Masuko, Naohisa; Imafuku, Hitomi; Egi, Moritoki; Terai, Yoshito
Abstract: A 40‐year‐old primigravida woman with a monochorionic‐triamniotic (MT) triplet pregnancy was hospitalized due to threatened abortion at 16 gestational weeks. Polyhydramnios in two fetuses and oligohydramnios in the third supported a diagnosis of feto‐fetal transfusion syndrome (FFTS) at 23 weeks and 3 days of gestation. Severe dyspnea and liver dysfunction required intensive care unit admission and mechanical ventilation support, and abdominal compartment syndrome (ACS) caused by polyhydramnios was clinically diagnosed. When her general condition was not improved regardless of intensive care, the patient delivered the three fetuses by cesarean section at 23 weeks and 5 days gestation. Abdominal decompression was achieved with delivery, and the patient was discharged 13 days after operation without morbidity. This is the first case report of ACS caused by FFTS in a MT triplet pregnancy resulting in extremely preterm birth.